2016
DOI: 10.1007/s10854-016-5142-9
|View full text |Cite
|
Sign up to set email alerts
|

Electric and magnetic properties of Y-type Ba2Mg2Fe12O22 hexaferrites with various Co doping

Abstract: Y-type hexaferrites Ba 2 Mg 2-x Co x Fe 12 O 22 (x = 0.4, 0.8, 1.2, 1.6) were synthesized by solid state reaction method. The impedance spectrum, AC conductivity, and dielectric properties were investigated at various temperatures and in a wide range of frequency. The dielectric properties and AC conductivity have been explained on the basis of space charge polarization and the electric exchange between Fe 3? and Fe 2? as well as the hole hopping between Co 2? and Co 3? ions at octahedral side. The complex imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
4
2
0
Order By: Relevance
“…Saturation of the initial magnetization curves is seen (Figure 3c) at a magnetic field of 50 kOe, the magnetization values being 34.5 emu/g and 30.4 emu/g at 4.2 K and 300 K, respectively. The M (50 kOe) values for 300 K are close to those reported by Wu et al [38] and lie between the values reported for non-substituted Ba 2 Mg 2 Fe 12 O 22 (23 emu/g) and Ba 2 Co 2 Fe 12 O 22 (34 emu/g) [13,23]. The hysteresis curve at 300 K is very narrow (about 70 Oe), while H c is about 35 Oe.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Saturation of the initial magnetization curves is seen (Figure 3c) at a magnetic field of 50 kOe, the magnetization values being 34.5 emu/g and 30.4 emu/g at 4.2 K and 300 K, respectively. The M (50 kOe) values for 300 K are close to those reported by Wu et al [38] and lie between the values reported for non-substituted Ba 2 Mg 2 Fe 12 O 22 (23 emu/g) and Ba 2 Co 2 Fe 12 O 22 (34 emu/g) [13,23]. The hysteresis curve at 300 K is very narrow (about 70 Oe), while H c is about 35 Oe.…”
Section: Resultssupporting
confidence: 89%
“…For the substitution degree x = 1.6, we observed that the first magnetic structure change was shifted to the higher temperature range. An increase of this transition temperature, as well as the saturation magnetization M s , by increasing the Co content was reported by Wu et al [38] in their study on Ba 2 Mg 2− x Co x Fe 12 O 22 ( x = 0.4, 0.8, 1.2, 1.6); but as shown above, we observed in addition that the shift was rather sensitive to the applied magnetic field. This should be related to the magnetic anisotropy which is both temperature and magnetic-field dependent.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…3,4 BADCy was blended with 4,4 ′ -bismaleimidodiphenyl methane (BMI) to obtain an interpenetrating polymer network which could be doped with organo-modified 2D montmorillonite nanoparticles to enhance the mechanical properties, thermal properties and dielectric property of the BMI/BADCy matrix. 5 However, a high curing temperature is one of the drawbacks of cyanate ester resins, which causes residual thermal stress in the products. Therefore, decreasing the curing temperature has been one of the main topics of study in the sustainable development of cyanate ester resins.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan in medicine and pharmacy is mostly applied in form of physical or chemical hydrogels. [25][26][27][28][29][30] Their obtainment is connected with the usage of various crosslinking agents like 1ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDS) leading to brosis and inammation. 31 Alternatively, glutaric aldehyde or genipin were used which resulted in signicant decrease of susceptibility of the material to biological degradation, hydrophilicity and adhesiveness.…”
mentioning
confidence: 99%